(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2016)
In this paper we give an overview of some routing protocols which can improve the efficiency and scalability of wireless sensor networks. The Wireless Sensor Network (WSN) is a network consisting of ten to thousand small nodes with sensing, computing and wireless communication capabilities. WSN are generally used to monitor activities and report events, such as pollution parameters, healthcare issues, fire info etc. in a specific area or environment. It routs data back to the Base Station (BS). Data transmission is usually a multi-hop from node to node towards the BS. This type of networks is limited in power, computational and communication bandwidth. The main goal of all researchers is to find out the energy efficient routing protocol which will improve considerably networks resources in term of prolonging lifetime of sensor nodes. Also we highlight the various routing protocol with advantages and limitations as well.